REKAYASA DATABASE TERDISTRIBUSI PADA LAYANAN PEMESANAN TIKET PESAWAT TERBANG - Lenti, Febri Nova (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2014)
Distributed database allows users at each location are dispersed can access data stored in another location. Advantages compared with a web-based database is if a database failure at one location then not will disable all other database operations. In addition, a distributed database has the readability of the data better than the centralized database, for the reason each site only handle a portion of the entire database , resulted in an difference to service the CPU and I /O such as the characteristics of the centralized database. The airlines as an organization that has branches and sales agents scattered in a few places if you want to always maximize service to its customers, it would be very appropriate if you are using a distributed database in a ticket booking transaction services. In this paper will be engineering a distributed database on tickets booking services . Implementation is done by applying a distributed database replication and applications performed using a sequential process model with object-oriented paradigm . Final result of the application of an airplane ticket booking services based distributed database that will improve the performance of the services.